Finite Element Analysis of Low Velocity Behaviour on Fused Deposition Modeling Printed Stab-Resistant Body Armour Design Features - Maidin, S.; Chong, S. Y. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Body armour is mainly worn to protect the human torso from attacks caused by weapons or projectiles. Despite a number of modern body armours have been developed, historical issue continue to exist and challenge the current protective solutions. However, additive manufacturing (AM) technology yet to be explored widely in attempt to address these issues. This research therefore investigates the feasibility of using AM system, specifically fused deposition modelling (FDM) process to manufacture textile geometrical models, which can be used for the development of novel user fit stab-resistant body armour. This study analyses the design features that could potentially influence the stab protection performance of FDM printed textile featuring an imbricated layout. This paper presents a finite element analysis to investigate the deformation distributed in the imbricated scale-like assemblies due to the knife blade penetrated through the overlapping scales vary with different scale thicknesses and overlapping angles. The results shows that 4mm model constructed in overlapping angle of 20˚ absorbed the most energy during the knife blade penetration. A weak region is found in between the overlapping scale of the single layer stab resistant model which could potentially allow the penetration of knife blade to cause injury.